Induction of apoptosis in human leukemia K562 cells by alpha-anordrin - Lou Li-Guang; Xu Bin (Acta Pharmacologica Sinica, 2016)
AIM: To study antitumor action of alpha-anordrin (Ano). METHODS: Morphological assessment of apoptosis was performed with light microscope and electron microscope. Membrane integrity was determined by trypan blue exclusion method. Endonucleolysis was assessed by agarose gel electrophoresis and flow cytometric methods. RESULTS: Exposure of exponentially growing K562 cells to Ano 2.5-50 mumol.L-1 for 48 h resulted in growth arrest, Ano 50 mumol.L-1 inhibited the growth of K562 cells by 67%. Cells were mainly blocked to progress through S-phase and arrested at G1 phase. After treatment of K562 cells with Ano, marked morphological changes including condensed chromatin, nuclear fragmentation, and reduction in volume were observed. Agarose gel electrophoresis of DNA from cells treated with Ano for 24-48 h revealed ""ladder"" pattern, typical features of apoptosis, and near 70% of cells underwent apoptosis as determined by flow cytometry. The S-phase cells were more susceptible to apoptosis. Despite extensive cleavage of DNA and nuclear fragmentation, the cell membrane of Ano-treated cells remained intact, excluding trypan blue. Apoptotic cells were detected as early as 8 h after Ano (50 mumol.L-1) treatment. CONCLUSION: Ano induces apoptosis in K562 cells.